PENGARUH PENGEMBANGAN KARIR TERHADAP KEPUASAN KERJA KARYAWANPADA UNIVERSITAS WIDYA GAMA MAHAKAM SAMARINDA - Iis Andriani (OBOR: Oikonomia Borneo, 2019)
The purpose of this study was to determine the effect of Career Development on Employee Job Satisfaction at Widya Gama Mahakam University Samarinda. This research method is associative by using statistical analysis tools with the help of SPSS version 24 computer program to determine the effect of each variable. From the results of the analysis, it is known that the Linear Regression value is Y = 1.908 + 0.525X, the coefficient of determination is 20%. The results of the t-test of career development variables have a positive and significant effect on employee job satisfaction (sig of 0.001 < 0.05 and t value of 3.574> t table 2.007)